Muscle mitochondrial stress adaptation operates independently of endogenous FGF21 action - Mario Ost; Verena Coleman; Anja Voigt; Evert M. van Schothorst; Susanne Keipert; Inge van der Stelt; Sebastian Ringel; Antonia Graja; Thomas Ambrosi; Anna P. Kipp; Martin Jastroch; Tim J. Schulz; et al. (Elsevier, 2016)
Objective: Fibroblast growth factor 21 (FGF21) was recently discovered as stress-induced myokine during mitochondrial disease and proposed as key metabolic mediator of the integrated stress response (ISR) presumably causing systemic metabolic improvements. Curiously, the precise cell-non-autonomous and cell-autonomous relevance of endogenous FGF21 action remained poorly understood. Methods: We made use of the established UCP1 transgenic (TG) mouse, a model of metabolic perturbations made by a specific decrease in muscle mitochondrial efficiency through increased respiratory uncoupling and robust metabolic adaptation and muscle ISR-driven FGF21 induction. In a cross of TG with Fgf21-knockout (FGF21−/−) mice, we determined the functional role of FGF21 as a muscle stress-induced myokine under low and high fat feeding conditions. Results: Here we uncovered that FGF21 signaling is dispensable for metabolic improvements evoked by compromised mitochondrial function in skeletal muscle. Strikingly, genetic ablation of FGF21 fully counteracted the cell-non-autonomous metabolic remodeling and browning of subcutaneous white adipose tissue (WAT), together with the reduction of circulating triglycerides and cholesterol. Brown adipose tissue activity was similar in all groups. Remarkably, we found that FGF21 played a negligible role in muscle mitochondrial stress-related improved obesity resistance, glycemic control and hepatic lipid homeostasis. Furthermore, the protective cell-autonomous muscle mitohormesis and metabolic stress adaptation, including an increased muscle proteostasis via mitochondrial unfolded protein response (UPRmt) and amino acid biosynthetic pathways did not require the presence of FGF21. Conclusions: Here we demonstrate that although FGF21 drives WAT remodeling, the adaptive pseudo-starvation response under elevated muscle mitochondrial stress conditions operates independently of both WAT browning and FGF21 action. Thus, our findings challenge FGF21 as key metabolic mediator of the mitochondrial stress adaptation and powerful therapeutic target during muscle mitochondrial disease. Author Video: Author Video Watch what authors say about their articles Keywords: Browning, FGF21, GDF15, Myokine, Mitochondrial disease, Muscle mitohormesis